TINJAUAN YURIDIS COVERNOTE HAK TANGGUNGAN YANG DIBUAT OLEH NOTARIS/PPAT DI KABUPATEN BANJAR PROVINSI KALIMANTAN SELATAN - , HERRY ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The research aims at determining the validity the covernote issued by Notary/ Land Deed Officer for two purposes. The first purpose is to find out some obstacles that bank faces in finishing the settlement of Hak Tanggungan (Mortage Right) whose covernote is issued by the Notary/ Land Deed Officer, and the second purpose is to explain steps that Bank will undergo when debtor is default while Mortgage has not been installed. This research is a juridical/empirical research. In this research, data are collected by performing literary and field research. Literary review is performed to obtain supporting data in the form of secondary data while field research is performed to obtain primary data. Literary research is conducted through document study and literary reviews